KANDUNGAN LOGAM BERAT TOTAL Pb DAN Cd DALAM SEDIMEN DAN BUAH PEDADA (Sonneratia alba) DI MUARA SUNGAI BADUNG - N. K.D.S. Widari; I M. Siaka; I. E. Suprihatin (Jurnal Kimia (Journal of Chemistry), 2019)
This paper discusses the total contents of Pb and Cd metals in sediment and pedada fruit (Sonneratia alba) collected from Estuary of Badung River. Wet digestion method using reverse aqua regia was performed to extract the metals. All metals were measured using Atomic Absorption Spectrophotometer (AAS). The results showed that the total contents of Pb and Cd in the sediments were 288.0131-376.0544 and 1.4849-7.0230 mg/kg, respectively, while in the pedada fruit were 160.0212-245.4012 and 3.8151-14.6917 mg/kg, respectively. Based on the results, the content of Pd and Cd in the sediment and pedada fruit in the area of Badung River Estuary exceeded the limits allowed indicating that the sediment and the pidada fruts are polluted by Pb and Cd metals